1996
DOI: 10.1038/bjc.1996.658
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of MRP-associated efflux of rhodamine 123 by genistein and related compounds

Abstract: Summary Multidrug resistance (MDR), caused by overexpression of either P-glycoprotein or the multidrug resistance protein (MRP), is characterised by a decreased cellular drug accumulation due to an enhanced drug efflux. In this study, we examined the effects of genistein and structurally related (iso)flavonoids on the transport of rhodamine 123 (Rhl23) and daunorubicin in the MRP-overexpressing MDR lung cancer cell lines COR-L23/R and MOR/R. Genistein, genistin, daidzein and quercetin showed major differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 15 publications
6
23
0
Order By: Relevance
“…4 intrinsic ability to be transported by Pgp (Figures 1, 2, 3). Although Rh123 has been shown to be a substrate for both Pgp and MRP1 (Twentyman et al, 1994;Versantvoort et al, 1996), we have shown predominant Pgp activity in Calu-3 cells (Hamilton et al, 2001b) using this marker compound.…”
Section: Introductionmentioning
confidence: 99%
“…4 intrinsic ability to be transported by Pgp (Figures 1, 2, 3). Although Rh123 has been shown to be a substrate for both Pgp and MRP1 (Twentyman et al, 1994;Versantvoort et al, 1996), we have shown predominant Pgp activity in Calu-3 cells (Hamilton et al, 2001b) using this marker compound.…”
Section: Introductionmentioning
confidence: 99%
“…This dye was early used as a mitochondrial marker, but because it is transported by ABCB1, and because cells that overexpress this protein accumulate much less Rho123, it became largely used to evaluate ABCB1 activity, including in renal cells and isolated perfused PT [10, 16, 17]. However, some authors observed that it might also be carried by the organic cation transporter system (OCT), which is not inhibited by CSA [18, 19], and by the MRP1 (or ABCC1) protein, which may be moderately inhibited by CSA [20, 21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…72 Other modulators such as genistein, a specific inhibitor of tyrosine kinase, or 7-chloro-4-notrobenz-2-oxa-1,3-diazole (NBD), a vacuolar H+-ATPase, have been reported to modulate MRP1 of a non-specific manner. [73][74][75] However, genistein showed major differences in effects on Rh123 vs DNR transport in the MRP1-mediated MDR cell lines: the accumulation of DNR was increased, whereas the accumulation of Rh123 was decreased by genistein. 73 Recently, van der Kolk et al 40 and ourselves 11 have demonstrated that MRP1 was functional in fresh acute myeloid leukemic blast cells using CF and calcein-AM, respectively.…”
Section: Mrp1 Activity In Amlmentioning
confidence: 98%
“…[73][74][75] However, genistein showed major differences in effects on Rh123 vs DNR transport in the MRP1-mediated MDR cell lines: the accumulation of DNR was increased, whereas the accumulation of Rh123 was decreased by genistein. 73 Recently, van der Kolk et al 40 and ourselves 11 have demonstrated that MRP1 was functional in fresh acute myeloid leukemic blast cells using CF and calcein-AM, respectively. We have also seen that some substrates of MRP1 were also substrates of Pgp (calcein-AM, CF, ±Rh123 etc).…”
Section: Mrp1 Activity In Amlmentioning
confidence: 98%